Practical Guidelines for Scientific Application of Uncrewed Aerial Vehicles in Svalbard (UAV Svalbard 3) - Hann, Richard; Betlem, Peter; Deja, Kajetan; Ewertowski, Marek; Harm-Altstädter, Barbara; Jonassen, Marius; Lampert, Astrid; Laska, Michal; Sobota, Ireneusz; Storvold, Rune; Tomczyk, Aleksandra; Zagorski, Piotr (Svalbard Integrated Arctic Earth Observing System, 2023)
This is chapter 6 of the State of Environmental Science in Svalbard (SESS) report 2022. Uncrewed aerial vehicles (UAVs), or drones, have become an established tool for a wide range of scientific applications. Today, UAVs are used for example for mapping geomorphic features, glaciers, and heritage sites, counting reindeer, atmospheric measurements, sea ice monitoring and in many other ways. However, the technology is still relatively new and there is a substantial untapped potential for using UAVs for scientific goals. This report’s main focus is to highlight practical issues related to planning and conducting fieldwork in Svalbard, as well as storing and sharing drone-based datasets. One of the key challenges in the field is related to a lack of standardised data storage and metadata requirements. This means that many datasets are not adequately described and/or archived so they are publicly available This means that drone-based data can often not be reused, for example for long-term monitoring studies. The practical recommendations about planning and conducting fieldwork with UAVs in Svalbard is intended to help and guide scientists to become more successful in conducting drone missions. Svalbard has several special challenges related to its remoteness, high latitude, and fauna. Recommendations are given on how SIOS can strengthen and expand scientific drone applications in Svalbard. The recommendations are intended to make it easier to conduct more complex missions in Svalbard and to train and fund new users. Furthermore, it is recommended to create a forum for scientists to discuss drone-related issues, e.g. to develop community standards for data.